Geographical distribution, environmental characteristics and valuation possibilities of the areas that have gained viticulture potential in Romania as a result of climate change - Liviu Mihai IRIMIA; Cristian Valeriu PATRICHE (Present Environment and Sustainable Development)
Climate change leads to the modification of the climatic conditions that have defined the specific of Romania wine regions. Using a GIS based methodology for evaluating the viticultural potential of geographical areas, this research reveals: the geographical distribution in Romania of the areas that acquired viticulture potential during the 1991-2013 time period; the possibilities of exploiting these areas in relation to the current land use; the grape varieties that could be grown and the types of wine that could be produced in these areas. According to the results of this research, during the 1991-2013 time period the total area with viticulture potential is, at Romanian level, with 25,245 km2 larger than during the 1961-1990 time period. The areas that acquired viticultural potential are mostly located in the northern half of Romania and at altitudes exceeding 550 m asl. Analyzed in relation to the type of current land use, from the area that has acquired viticultural potential, 11,408 km2 are excluded from the possibility of viticultural use, being occupied by forests, water bodies and industrial and residential constructions. The difference of 13,837 km2 corresponds to agricultural lands of which 8,700 km2 could be exploited through viticulture if this would be considered by land owners a more economically efficient alternative of capitalizing on them.